2016
DOI: 10.1080/10962247.2016.1218393
|View full text |Cite|
|
Sign up to set email alerts
|

Trends and spatial patterns of fine-resolution aerosol optical depth–derived PM2.5 emissions in the Northeast United States from 2002 to 2013

Abstract: Emission trend analysis provides crucial information for evaluating and enhancing the efficacies of emission control strategies as well as studying air pollution associated health risks. In this study, the patterns and trends of year-round and seasonal PM emission over the Northeast United States are presented at a spatial resolution of 1 km × 1 km for the period of 2002-2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The results obtained in the present study are comparable to some previous studies like Soni et al (2018), Sreekanth et al (2017, Chen et al (2013) and Shaw and Gorai (2018) etc. There are various other techniques like support vector regression (Kisi et al 2017;Liu et al 2017) and land use based regression techniques (Liu et al 2016;Tang et al 2017) used by many other studies and results obtained in those studies are comparable to the results obtained in the present study. Hence present methodology can be used for the estimation of PM 2.5 at ground level and other techniques can be used to compare and validate present results which can be considered as future scope.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results obtained in the present study are comparable to some previous studies like Soni et al (2018), Sreekanth et al (2017, Chen et al (2013) and Shaw and Gorai (2018) etc. There are various other techniques like support vector regression (Kisi et al 2017;Liu et al 2017) and land use based regression techniques (Liu et al 2016;Tang et al 2017) used by many other studies and results obtained in those studies are comparable to the results obtained in the present study. Hence present methodology can be used for the estimation of PM 2.5 at ground level and other techniques can be used to compare and validate present results which can be considered as future scope.…”
Section: Discussionsupporting
confidence: 90%
“…The correlation was found to be significant, with a value of 0.65 during the study period. Tang et al (2017) observed trends in temporal and spatial patterns of PM 2.5 derived from satellite-derived AOD products over a study period of 2002-2013 in the north-eastern United States. AOD from MODIS, meteorological parameters like T, surface level BLH and RH are considered from North America Regional Reanalysis (NARR), and land use variables like vegetation and population are considered to develop a land use regression-based model.…”
Section: Introductionmentioning
confidence: 86%
“…Among these three factors, human activities, such as vehicle exhaust emission and industrial production 7 , 8 , are the dominant factors of PM 2.5 pollution 9 . Natural environment, such as meteorological conditions (e.g., precipitation and wind speed) 10 , facilitate the transportation and diffusion of PM 2.5 , while atmospheric chemical reactions stimulate the secondary formation of PM 2.5 11 . All of these factors interact with PM 2.5 at different spatial and temporal scales, and thus can have varying effects on PM 2.5 distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Regression models initially were used for predictive tasks. Tang et al [18] applied a linear regression method to predict PM2.5 emissions in the Northeast United States from 2002 to 2013 based on fine-resolution aerosol optical depth. Oteros et al [19] used different factors of pollen concentration and took into account the extreme weather events in the Mediterranean climate characteristics to establish a multivariate regression model.…”
Section: Related Workmentioning
confidence: 99%